2020
DOI: 10.3390/cells9102231
|View full text |Cite
|
Sign up to set email alerts
|

Selinexor Sensitizes TRAIL-R2-Positive TNBC Cells to the Activity of TRAIL-R2xCD3 Bispecific Antibody

Abstract: Triple-negative breast cancer (TNBC) is an aggressive disease with poor prognosis and limited therapeutic options. Recent advances in the immunotherapy field have enabled the development of new treatment strategies, among which the use of bispecific antibodies (BsAbs), able to redirect T cells against tumors, has shown promising results. In particular, a BsAb that uses TNF-related apoptosis-inducing ligand receptor 2 (TRAIL-R2) as a target was constructed and demonstrated good results in redirecting CD3+ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In addition to NK cells, inhibition of NKG2A has also been shown to enhance the efficacy of cancer vaccines in murine tumor models via CD8+ T cell activation ( 58 ) and therefore selinexor mediated HLA-E downregulation may also promote T cell activity. Interestingly, previous studies have revealed that selinexor pre-treatment increase T cell activation against B cell malignancies ( 28 ) and breast cancer cells ( 27 ) however the contribution of HLA-E/NKG2A interactions in these settings were not investigated. Based on our data, it is plausible that this may have been due to disruption of the NKG2A:HLA-E axis by selinexor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to NK cells, inhibition of NKG2A has also been shown to enhance the efficacy of cancer vaccines in murine tumor models via CD8+ T cell activation ( 58 ) and therefore selinexor mediated HLA-E downregulation may also promote T cell activity. Interestingly, previous studies have revealed that selinexor pre-treatment increase T cell activation against B cell malignancies ( 28 ) and breast cancer cells ( 27 ) however the contribution of HLA-E/NKG2A interactions in these settings were not investigated. Based on our data, it is plausible that this may have been due to disruption of the NKG2A:HLA-E axis by selinexor.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical trials are also ongoing to assess selinexor for the treatment of solid tumors and hematological malignancies ( 20 ), including in combination with anti-CD20 antibodies for patients with advanced B cell non-Hodgkin lymphoma (NCT03147885) ( 26 ). In addition to its direct cytotoxicity against tumor cells, selinexor has also been described to sensitize breast cancer cells to T cell attack in combination with a TRAIL-R2xCD3 bispecific antibody ( 27 ) and to increase CAR T cell activity against CD19 positive malignant B cells ( 28 ). The effect of selinexor or XPO1 inhibition on cancer cell sensitivity to NK cell activity however has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this table also includes CD3-BsAb formats based on affinity-enhanced TCR-like domains that recognize peptide–human leukocyte antigen (HLA) complexes (immune mobilizing monoclonal T-cell receptors against cancer (ImmTACs)) [ 42 ]. Multiple other TAAs are currently pursued in preclinical studies hoping to make their way to the clinic, including B7-H4, CD133, CD155, claudin 6 (CLDN6), cellular mesenchymal to epithelial transcription factor (C-MET), ephrin receptor A10 (EphA10), folate receptor 1 (FOLR1), HLA-A*24:survivin 2B 80-88 , integrin β4 (ITGB4), P-cadherin, prolactin receptor (PRLR), receptor tyrosine kinase-like orphan receptor 1 (ROR1), TNF-related apoptosis-inducing ligand receptor (TRAIL-R2), transferrin receptor (TfR) and tumor-associated calcium signal transducer 2 (Trop-2) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Main Textmentioning
confidence: 99%
“…Whether SINEs also specifically activates NKG2A+ T cells against cancer cells has not been addressed although they can enhance the anti-tumour activity of CD19 directed CAR T cells against multiple lymphoma cell lines [109] and TRAIL-R2xCD3 bispecific antibodies against breast cancer cells [110]. In summary, XPO1 inhibition primes cancer cells for NK cell mediated cytotoxicity via HLA-E downregulation, and SINEs in combination with NK cell directed therapies has potential to promote anti-tumour responses in patients.…”
Section: Selective Inhibition Of Nuclear Exportmentioning
confidence: 99%